High-temperature stable fiber Bragg gratings with ultra strong cladding modes written using the phase mask technique and an infrared femtosecond laser: erratum - Abdukerim, Nurmemet; Grobnic, Dan; Hnatovsky, Cyril; Mihailov, Stephen J (Optics letters, 2020)
In this erratum, we correct the mistakes in Eqs. (2) and (2a) in Opt. Lett.45, 443 (2020).OPLEDP0146-959210.1364/OL.381111.